2019
DOI: 10.21037/tlcr.2019.12.19
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of non-small cell lung cancer and histoplasmosis pulmonary nodules: insights from radiomics model performance compared with clinician observers

Abstract: Background: Histoplasmosis pulmonary nodules often present in computed tomography (CT) imaging with characteristics suspicious for lung cancer. This presents a work-up decision issue for clinicians in regions where histoplasmosis is an endemic fungal infection, when a nodule suspicious for lung cancer is detected.We hypothesize the application of radiomic features extracted from pulmonary nodules and perinodular parenchyma could accurately distinguish between suspicious histoplasmosis lung nodules and non-smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…SUV max , a metabolic PET parameter, might barely differentiate these two conditions as to vast aggregation of activated macrophages and lymphocytes promotes high 18 F-FDG avidity in both conditions [ 100 , 101 ]. Addressing these issue, a research team demonstrated that personalised and distinctive diagnosis of solid active pulmonary TB and solid LC might be performed using the radiomics nomogram [ 102 ].…”
Section: Application Of 18 F-fdg Pet/ct Radiomicsmentioning
confidence: 99%
“…SUV max , a metabolic PET parameter, might barely differentiate these two conditions as to vast aggregation of activated macrophages and lymphocytes promotes high 18 F-FDG avidity in both conditions [ 100 , 101 ]. Addressing these issue, a research team demonstrated that personalised and distinctive diagnosis of solid active pulmonary TB and solid LC might be performed using the radiomics nomogram [ 102 ].…”
Section: Application Of 18 F-fdg Pet/ct Radiomicsmentioning
confidence: 99%
“…General characteristics of the two groups were almost similar except that participants undergoing mobile LDCT screening were a bit older. Age is considered to be an important factor involved in the number of nodules (35,36). The probability of developing lung cancer also increased with aging (37).…”
Section: Discussionmentioning
confidence: 99%
“…For this model, its predictions showed that the AUC reached 0.75 (followed up for 2 years) and 0.83 (1 year follow-up), and this method was superior to the traditional image evaluation and CADaided analysis (33). In addition, radiomics analyses are also used to differentiate lung cancer from benign diseases, such as nodular granuloma and infectious nodules, in order to improve the diagnostic accuracy of pulmonary nodules (34)(35)(36). These studies further confirm the application value of radiomics analyses in the determination of pulmonary nodules' benign and malignant properties and also lay the foundation for the subsequent clinical analysis of the pulmonary nodules' properties.…”
Section: Application Of Radiomics In the Analysis Of Pulmonary Nodulesmentioning
confidence: 94%